Зображувальний документ як вид письмових доказів в госопдарському процесуальному праві - Гаврилова, А. А.; Гаврилова, А. А.; Gavrilova, А. (My University, 2012)
Having studied scientifi c literature, regulatory acts and judiciary practice, the defi nition of written evidences has been given, they have been classifi ed by various attributes. The Article determines the place of written evidences in general classifi cation of evidences, their difference in contrast to other evidences is shown, the detailed analysis of national legislation on issues of written evidences types used in economic procedure has been performed.
Гаврилова А. А. Зображувальний документ як вид письмових доказів в госопдарському процесуальному праві /А. А. Гаврилова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 396-402.
Keywords: господарський процес в Україні; письмові докази у господарському процесі; класифікація письмових доказів; хозяйственный процесс Украины; письменные доказательства в хозяйственном процессе; классификация письменных доказательств; economic process in Ukraine; written evidence in the economic process; Classification of written evidence